L’évaluation des trames vertes urbaines : apports et limites de la socio-économie des transports - Jacques Stambouli (Développement Durable et Territoires)
The terminology used for the definition of urban greenways (project, developed infrastructure, flows, corridors, improvement of living conditions, local authorities) is reminiscent of the transport infrastructures, fixed elements of a network for the movement of people and goods inside territories. This article examines the contribution of socio-economic evaluation methods of transport infrastructures to evaluate, by developers, the urban greenways. It highlights the limits of these methods for the urban greenways, because of the plurality of ecosystem services related to biodiversity, the diversity of stakeholders and scales of development. It advocates a spatial pluralistic Multi-criteria evaluation method, with monetary and non-monetary items, and takes into consideration the conditions for a democratic evaluation.